Differential Functions of Pepper Stress-Associated Proteins in Response to Abiotic Stresses - Bae, Yeongil; Lim, Chae Woo; Lee, Sung Chul (Frontiers in Plant Science, 2021)
Stress-associated proteins (SAPs), a group of zinc-finger-type proteins, have been identified as novel regulators of plant abiotic and biotic stresses. However, although they have been discovered in different plant species, their precise functional roles remain unclear. Here, we identified 14 SAP subfamily genes in the pepper genome. An investigation of the promoter regions of these genes for cis-regulatory elements associated with abiotic stress responses revealed the presence of multiple stress-related elements. Domain and phylogenetic analyses using the corresponding protein sequences revealed that the CaSAP genes can be classified into six groups (I to VI) and sorted into two broad types. Expression levels of the CaSAP genes were found to be differentially induced by low temperature, the dehydration stress, or exogenous abscisic acid. Group II and IV genes were highly induced by the low temperature and dehydration treatments, respectively. Moreover, subcellular localization analysis indicated that the proteins in these two groups are distributed in the nucleus, cytoplasm, and plasma membrane. Among the pepper plants silenced with the three identified group II CaSAP genes, the CA02g10410-silenced plants showed tolerance to low temperature, whereas the CA03g17080-silenced plants were found to have temperature-sensitive phenotypes. Interestingly, group IV CaSAP-silenced pepper plants showed drought-tolerant phenotypes. These findings contribute to a preliminary characterization of CaSAP genes and provide directions for future research on the biological role of CaSAPs in response to different abiotic stresses.